Fireproof paper or sheet

JP2025022556APending Publication Date: 2025-02-14IMAE KOUGIYOU KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023127245
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0018】 本発明の不燃紙又は不燃シートは、火炎に暴露されても発火·燃焼することなく、火炎暴露後も紙又はシートとしての形状を保持できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022556000001_ABST
    Figure 2025022556000001_ABST
Patent Text Reader

Abstract

To provide a fireproof paper or sheet, which hardly causes ignition or burning, and can maintain a sheet-shape even when exposed to flames of nearly 1000°C.SOLUTION: There is provided a fireproof paper or sheet, comprising: a silica-based inorganic fiber; a layer-shaped silicate mineral; an organic fiber; and optionally a glass fiber, wherein at least some of the silica-based fiber, the organic fiber, and the glass fiber are entangled in a planar direction, and some of the organic fiber are fused in a thickness direction or the planar direction. The layer-shaped silicate mineral is preferably a fibrous clay mineral. Moreover, the fireproof paper or sheet is preferably produced by wet papermaking.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a non-flammable paper or sheet that does not ignite even when exposed to flames and has flame resistance and fire prevention properties. [Background technology]

[0002] Non-flammable paper or sheets are used as fire and flame resistance measures for buildings, and for fire and flame resistance measures for equipment and devices that may catch fire. Known examples of non-combustible papers include glass fiber paper made by forming glass fibers into sheets using a wet papermaking method, sheets using highly heat-resistant resin fibers such as aramid fibers, and non-combustible papers that have been made self-extinguishing by incorporating a high content of compounds containing crystal water such as aluminum hydroxide.

[0003] High heat resistant resin fibers are not flammable, but they undergo oxidative decomposition and carbonization at around 400°C, and therefore cannot be used in applications where they are exposed to atmospheres of 500°C or higher or to flames.

[0004] Although glass fiber paper does not generate combustion gases, the melting point of the general-purpose E-glass fiber is around 800°C, and it starts to soften at around 700°C. Therefore, when exposed to high temperatures of 700°C or more due to exposure to flames, the fiber shape cannot be maintained, and as a result, the sheet shape cannot be maintained. Aluminum hydroxide can impart self-extinguishing properties by an endothermic dehydration reaction at about 200 to 300° C. However, in order to impart the desired non-combustibility, it is necessary to blend a large amount of aluminum hydroxide, and there is a problem that a sheet blended with a large amount of aluminum hydroxide cannot ensure the strength required for paper or sheets.

[0005] Regarding non-combustibility, Patent No. 5275602 (Patent Document 1) proposes a non-combustible sheet that can comply with the heat generation test of the Building Standards Act and has sufficient bending strength. The non-combustible sheet is obtained by wet-sheeting a raw material slurry containing a combination of inorganic fibers, cellulose fibers, and sepiolite, as well as 30 to 85 mass% (solid content) of steel slag alone, a combination of steel slag and calcium silicate, a combination of steel slag, calcium silicate and a hydrated inorganic compound, or a combination of steel slag and a hydrated inorganic compound, in the presence of a flocculant.

[0006] Patent Document 1 proposes using rock wool fiber, glass fiber, ceramic fiber or carbon fiber as inorganic fiber (paragraph number 0013), and discloses examples in which rock wool fiber and glass fiber are used. It is described that the non-combustibility is deteriorated when sepiolite is not contained, by comparing the examples with the comparative examples. However, no comparative examples are disclosed in which glass fiber is used as the inorganic fiber and sepiolite is not contained. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 5275602 Summary of the Invention [Problem to be solved by the invention]

[0008] In Patent Document 1, when glass fibers are used as the inorganic fibers, the glass fibers, which are the main constituent of the sheet, are unable to maintain their fiber shape when exposed to high temperatures of 700°C or higher due to flame exposure, and as a result, the inorganic particles such as steel slag are unable to maintain their sheet shape.

[0009] In this respect, rock wool has a higher melting point and excellent heat resistance than glass fiber, and can maintain its fibrous shape even when exposed to flames. Rock wool is manufactured by melting raw material slag or rock in an electric furnace at 1500 to 1600°C, blowing the molten material away with centrifugal force, and solidifying it in the air. Based on this manufacturing method, rock wool contains non-fibrous particles (shot) that could not be fully turned into fibers. Although such non-fibrous particles can be reduced during the papermaking process, it is difficult to completely remove them, so it is unavoidable that they will be mixed into non-combustible paper or sheets at a certain rate. Such non-fibrous particles may scratch and damage the surfaces of objects that come into contact with the paper or sheet. In the case of sound-absorbing covering materials, car body protection sheets used at automobile sheet metal work sites, and fireproof and flame-resistant sheets used in glass factories and foundries, there are issues with using rock wool, ceramic fibers, and alkaline earth silicate wool that contain shot, since non-fibrous particles may be mixed into the final product or damage the product.

[0010] The present invention has been made in consideration of the above circumstances, and its object is to provide a fire-resistant, non-combustible paper or sheet which will not ignite even when exposed to a flame of nearly 1000°C, can retain its shape for at least 10 minutes, and can prevent the inclusion of impurities. [Means for solving the problem]

[0011] The fire-retardant paper or sheet of the present invention may be embodied in the following manner. (1) A fire-retardant paper or sheet comprising: silica-based inorganic fibers; layered silicate minerals; and organic fibers, in which at least a portion of the silica-based fibers and the organic fibers are entangled in the planar direction, and a portion of the organic fibers are fused in the thickness direction or planar direction.

[0012] (2) The fire-retardant paper or sheet according to (1) further contains glass fibers, and a portion of the glass fibers is entangled with the silica-based fibers or the glass fibers.

[0013] (3) The fire-retardant paper or sheet according to (1) or (2), comprising 40 to 85% by weight of the silica-based inorganic fiber, 10 to 40% by weight of the layered silicate mineral, 3 to 10% by weight of the organic fiber, and 0 to 15% by weight of the glass fiber.

[0014] (4) In any one of the above (1) to (3), the layered silicate mineral is preferably a fibrous clay mineral.

[0015] (5) The fire-retardant paper or sheet according to any one of (1) to (4) above, which is produced by papermaking an aqueous suspension containing silica-based inorganic fibers, layered silicate minerals, organic fibers, and optionally glass fibers. It is preferable that the silica-based fibers, the organic fibers, and the optionally included glass fibers are arranged in a planar direction to form a layer.

[0016] (6) In the fireproof paper or sheet according to any one of (1) to (5) above, the thickness is preferably 0.3 to 10 mm.

[0017] (7) Bulk density: 150-400 kg / m 3 The fire-retardant paper or sheet according to any one of (1) to (6) above. Effect of the Invention

[0018] The fire-resistant paper or sheet of the present invention will not ignite or burn even when exposed to flame, and can retain its shape as paper or sheet even after exposure to flame. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is a diagram for explaining a flame exposure test 1 carried out in an example. [Diagram 2] FIG. 2 is a diagram for explaining a flame exposure test 2 carried out in the examples. [Diagram 3] FIG. 2 is a diagram for explaining a flame exposure test 2 carried out in the examples. [Figure 4] FIG. 1 is a diagram for explaining the handling properties in the examples. [Diagram 5]1 is an electron microscope photograph (100x) of a flat surface of No. 4 produced in the example. [Figure 6] 1 is an electron microscope photograph (70x) of a cross section cut along the thickness direction of No. 4 produced in the example. [Figure 7] 1 is an electron microscope photograph (100x) of a flat surface of No. 4 after flame exposure test 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The fire-retardant paper or sheet of the present invention contains silica-based inorganic fibers; fibrous minerals; organic fibers; and, optionally, glass fibers in predetermined proportions, and at least one of the silica-based inorganic fibers, the organic fibers, and the glass fibers are entangled in the surface direction, and a portion of the organic fibers is fused in the thickness direction or planar direction.

[0021] Furthermore, it is preferable that the silica-based inorganic fibers, the organic fibers, and the glass fibers are arranged to extend in a planar direction to form a layer. Specifically, it can be produced by wet papermaking an aqueous suspension (raw material slurry) containing silica-based inorganic fibers, fibrous minerals, organic fibers, and optionally glass fibers in predetermined proportions.

[0022] <Composition of raw material slurry (suspension for wet papermaking)> First, the raw material slurry that is the raw material for the fireproof paper or sheet of the present invention will be described. The raw material slurry contains silica-based inorganic fibers, fibrous minerals, organic fibers, and, if desired, glass fibers in predetermined proportions.

[0023] (1) Silica-based inorganic fibers The silica-based inorganic fiber used in the present invention contains SiO 2 The amorphous fiber contains 80% by weight or more, preferably 85% by weight or more, more preferably 90% by weight or more, and most preferably 95% by weight or more of SiO 2 Other components include 1-10% by weight of alumina, Na 2 O, ZrO2 , TiO 2 , Li 2 OK 2 O, CaO, MgO, SrO, BaO, Y 2 O 3 , La 2 O 3 , Fe 2 O 3 The silica-based inorganic fiber may contain 10% by weight or less of a metal oxide such as silica-based inorganic fiber, but the composition is such that the melting point of the silica-based inorganic fiber is above 1000°C, preferably 1200°C or higher, and more preferably 1300°C or higher.

[0024] The silica-based inorganic fiber used in the present invention is manufactured by cutting filaments to a predetermined fiber length, and based on the manufacturing method, the silica-based inorganic fiber used does not substantially contain non-fibrous particles. Specifically, the content of non-fibrous particles is less than 0.1% by weight, preferably less than 0.01% by weight.

[0025] As the silica-based inorganic fibers, commercially available products can be used, such as BELCOTEX (registered trademark) from BELCHEM GmbH.

[0026] BELCOTEX® is a silica-based amorphous fiber made from silicic acid modified with alumina, typically containing 90-97% by weight silica, about 3-9 weight percent alumina, less than 0.5 percent sodium oxide, and less than 0.5 percent other components (ZrO 2 , TiO 2 , Li 2 OK 2 O, CaO, MgO, SrO, BaO, Y 2 O 3 , La 2 O 3 , Fe 2 O 3 , and mixtures thereof). The melting point is in the range of 1500℃ to 1550℃. Such silica-based amorphous fibers are advantageous in that they are substantially free of non-fibrous particles (shot), which are a cause of deterioration and variation in characteristics.

[0027] BELCOTEX (registered trademark) has hydroxyl groups at its terminals and undergoes dehydration condensation when heat-treated at 300° C. or higher. In the present invention, it may be an untreated product (containing hydroxyl groups at its terminals) or a heat-treated product (wherein the hydroxyl groups at the terminals have been converted into siloxane bonds (Si-O-Si bonds) through dehydration condensation).

[0028] The silica-based fiber having the above-mentioned composition is used as a staple fiber having a diameter of 6 to 13 μm, preferably about 7 to 10 μm, and a length of 3 to 30 mm, or a staple fiber having a diameter of 6 to 13 μm, preferably about 7 to 10 μm, and generally a length of 1 to 50 mm, preferably 3 to 30 mm.

[0029] The solid content of the raw material slurry of the silica-based inorganic fibers is 40% by weight or more, 45% by weight or more, or 50% by weight or more, and 85% by weight or less, 80% by weight or less, 75% by weight or less, or 70% by weight or less.

[0030] (2) Clay minerals The clay mineral used in the present invention is one that has plasticity and flexibility in a slurry state, can penetrate into the gaps between fibers, can form a coating film when dried and solidified, and can function as a binder between fibers. Preferably, it is a layered silicate with excellent coating film forming properties.

[0031] Specifically, fibrous clay minerals such as sepiolite and palygorskite, hydrous ferrosilicate minerals such as bentonite, mica, kaolinite, smectite, montmorillonite, sericite, illite, glauconite, chlorite and talc, or mixtures thereof can be used. These are non-flammable and have high heat resistance, and therefore are useful for improving flame resistance and heat resistance.

[0032] Sepiolite and palygorskite are hydrated magnesium silicates with a 2:1 ribbon structure, and can be made into fine fibrous material by defibration processing. Sepiolite and palygorskite are classified into α-type and β-type based on their origin. α-type is caused by hydrothermal action under high temperature and pressure, has a high degree of crystallinity, and a high proportion of long fibers. β-type is caused by sedimentation on the bottom of shallow seas or lakes, has a low degree of crystallinity, and has a high proportion of short fibers (lumpy or clay-like form). Either α-type or β-type can be used, and they may be used mixed together.

[0033] Sepiolite has a layered structure with a chain structure, is porous, has a large non-surface area, and has excellent adsorption properties. It has thixotropy, and becomes fibrous when crushed in a slurry using water as a dispersion medium.

[0034] The fibrous form of sepiolite and palygorskite has a width equivalent to the fiber diameter of less than 0.1 μm, and the length (fiber length) that can be measured by microscopic observation is at most about 150 μm. Such fibrous clay minerals can be entangled with silica-based fibers and glass fibers in the raw material slurry, and can contribute to increasing the strength and flexibility of the sheet produced by papermaking.

[0035] Kaolinite is a dioctahedral 1:1 layered silicate, and the one with water molecules between the layers is sometimes called halloysite.

[0036] Bentonite is a natural clay mineral whose main component is montmorillonite. Smectite is a general term for a group of 2:1 type minerals, including montmorillonite, stevensite, and hectorite. Montmorillonite unit crystals are flat plate-like units consisting of tetrahedral sheets, octahedral sheets, and tetrahedral sheets, and multiple such unit crystals are stacked to form layers. Montmorillonite unit crystals are very thin plate-like crystals with a thickness of about 1 nm and a width of 100 to 1000 nm, so like smectite and sepiolite, they can penetrate into the gaps between fibers in the slurry, form a coating film when dried and solidified, and function as a binder for these. Montmorillonite has a high liquid limit and a high water content. Smectite has the property of swelling, where water or organic matter enters between the layers and expands, and can contain a large amount of water between the layers (for example, 10 times more water than kaolin).

[0037] The layered silicate as described above may exist as a powder having an average particle size of 300 μm or less, preferably 200 μm or less, more preferably 10 to 100 μm, in terms of circle equivalent diameter, before the slurry is prepared, but when mixed with water, it becomes viscous, adhesive, and plastic, and has the ability to form a coating film by itself. Therefore, when the raw material slurry is dried after being made into a paper, the clay can enter the gaps between the fibers, and when it is dried and solidified, it can form a coating film and function as a binder for these. In particular, these mineral clays are heat-resistant and flame-resistant, and therefore can function as binders for silica-based fibers even at high temperatures of 800°C or higher or long-term exposure to flames, at which the organic fibers described below are burned away, and even at temperatures at which glass fibers melt. Furthermore, when sepiolite or palygorskite, which is a clay having a fibrous form, is used, flexibility can be imparted to the sheet, which is preferable.

[0038] The content of the clay minerals in the raw material slurry and the noncombustible sheet is 10% by weight or more, 15% by weight or more, 20% by weight or more, and 40% by weight or less, 35% by weight or less, 30% by weight or less.

[0039] (3) Organic fibers The organic fibers used in the present invention are entangled with each other or with the silica-based fibers, and further with the glass fibers and heat insulating particles described below, during the papermaking process, and can thus act as a binder for these.

[0040] Examples of organic fibers that can be used include cellulose fibers, pulp fibers, polyester fibers (softening temperature: about 240°C, melting temperature: about 255 to 260°C), polypropylene fibers (softening temperature: about 140 to 160°C, melting temperature: about 165 to 173°C), polyethylene fibers (softening temperature: about 100 to 115°C, melting temperature: about 125 to 135°C), acrylic fibers (softening temperature: about 190 to 240°C), polyvinyl chloride fibers (softening temperature: about 60 to 100°C, melting temperature: about 200 to 210°C), vinylidene fibers (softening temperature: 145 to 165°C, melting temperature: about 165 to 185°C), nylon fibers (softening temperature: about 180°C, melting temperature: about 215 to 220°C), vinylon fibers (softening point: 220 to 230°C), and polyvinyl alcohol fibers. Alternatively, thermoplastic resin fibers having a core-sheath structure using fibers with a low softening temperature in the surface layer may be used.

[0041] These organic fibers impart strength to the wet sheet during papermaking, and after papermaking, in the heating and drying process, they are softened by heat, and further, part of the surface melts, and then hardened again by cooling after drying, so that part of the organic fibers fuses. This can suppress the springback of inorganic fibers, which have high resilience, in the pressurizing process in papermaking. In particular, when glass fibers are contained, suppressing the springback of the glass fibers can contribute to adjusting the thickness of the sheet to be finally obtained.

[0042] In addition, since organic fibers can soften not only during normal use but also when the temperature is increased, particularly before the glass fibers, when the organic fibers contain inorganic particles as described below, the organic fibers can soften in accordance with the retention state of the inorganic particles between the inorganic fibers, thereby making it possible to retain the inorganic particles in a more stable state.

[0043] The size of the organic fiber used in the present invention is not particularly limited, but staple fibers having a fiber diameter of 3 μm to 50 μm, preferably 5 μm to 30 μm, and a fiber length of 1 to 20 mm, preferably 3 to 10 mm, are preferably used. The organic fiber needs to be homogeneously entangled with the inorganic fiber that is the main component of the noncombustible sheet, so it is preferable that the organic fiber has a length similar to that of the inorganic fiber.

[0044] The organic fibers as described above should be contained in an amount necessary and sufficient to fix the entangled inorganic fibers and to impart flexibility to the sheet. If the content is too high, it will cause a decrease in non-combustibility and flame resistance. Therefore, the solid content in the raw material slurry is 3 to 10% by weight, preferably 5 to 8% by weight.

[0045] (4) Glass fiber When silica-based fibers having hydroxyl groups at their ends (unburned or untreated silica-based fibers) are used as the silica-based fibers, the hydroxyl groups undergo dehydration condensation at high temperatures, causing the silica-based fibers to shrink, i.e., undergo thermal shrinkage. Such thermal shrinkage of silica-based fibers can cause cracks and the like in the case of a specification in which a part of a sheet (paper) is fixed. In such a case, by coexisting glass fibers, the glass fibers melted by high temperature fill in the thermally contracted portions of the silica-based inorganic fibers, thereby preventing deformation and cracks caused by heating.

[0046] Therefore, when silica-based fibers having hydroxyl groups at their ends (unburned or untreated silica-based fibers) are used as the silica-based fibers, it is preferable that they contain glass fibers.

[0047] In addition, glass fibers have the effect of imparting tensile strength to the sheet during normal use (at a temperature at which the fibers do not soften or melt, usually 200°C or less). Therefore, whether untreated or heat-treated silica-based fibers are used, it is preferable that glass fibers are included. On the other hand, at high temperatures such as when exposed to a flame, the glass fibers melt and become fluid, making it impossible to maintain the fiber shape. From the viewpoint of the role of the molten glass fibers being trapped between the silica fibers to suppress sagging and offsetting the shrinkage of the silica-based fibers, when using uncalcined silica-based fibers, it is preferable to include 5 to 15% by weight.

[0048] The glass fibers used in the present invention are not particularly limited in type or size, but E-glass fibers are preferred from the standpoints of availability and cost. The fiber diameter is about 1 to 10 μm, preferably 3 to 8 μm, and more preferably 6 to 8 μm. The fiber length may be long enough and strong enough to be entangled with the silica-based fiber and the organic fiber described later. On the other hand, glass fiber melts at high temperatures such as when exposed to a flame, and if the glass lump produced by melting becomes too large, it will sag under its own weight. Therefore, it is preferable to use staple fiber with a fiber length of 1 to 15 mm, preferably 2 to 10 mm, as the glass fiber.

[0049] (5) Other ingredients In addition to the above components, the composition may contain, if desired, organic binders other than organic fibers (latex, polymer powder, etc.); inorganic binders; flocculants; mineral fibers other than clay minerals, and the like. When other components are contained, it is desirable to contain them in an amount of less than 20% by weight, preferably 10% by weight or less, and more preferably 5% by weight or less. When organic components are contained, it is desirable to contain them in an amount that does not impair the non-flammability according to the present invention (less than 8% by weight, preferably 5% by weight or less).

[0050] (5-1) Flocculant The flocculant used in the present invention promotes the formation of flocs of the components in the raw material slurry by cross-linking adsorption action or the like, and improves the deposition of fibers or particles on the papermaking screen, and is also called a retention improver or fixing agent.

[0051] Examples of the flocculant include organic flocculants such as polyacrylamide, polysodium acrylate, polyamine, polymethacrylic acid ester, dicyandiamide, polyethyleneimine, chitosan, and cationic starch, and inorganic flocculants such as aluminum sulfate and polyaluminum chloride. Any of these may be used, or a mixture of the two may be used.

[0052] The flocculant is preferably added in an amount of about 0.005 to 5 parts by weight, calculated as solid content, relative to 100 parts by weight of the total solid content in the raw material slurry.

[0053] (5-2) Organic binder The organic binder that can be used in the present invention can be in various forms such as powder, granules, colloidal solution, high viscosity fluid, and the like. Specific examples of the polymer include powdery or fluid polymers, such as latexes such as acrylic latex and (meth)acrylic latex; powdery thickening substances such as polyvinyl alcohol powder and starch; copolymers of styrene and butadiene, vinylpyridine, acrylonitrile, and copolymers of acrylonitrile and styrene.

[0054] (5-3) Inorganic binder Examples of the inorganic binder include colloidal silica, water glass, calcium silicate, silica sol, alumina sol, and alkoxysilane. These inorganic binders can be used as binders between inorganic fibers together with or in place of organic binders.

[0055] (5-4) Mineral fibers other than clay minerals The mineral fiber referred to here is a mineral fiber other than fibrous clay that has thixotropy in a slurry and has film-forming properties, specifically, wollastonite and potassium titanate whisker.

[0056] Wollastonite is a needle-shaped crystalline mineral (metasilicate) with a width, equivalent to the fiber diameter, of less than 1 μm and a length of about 50 μm. Potassium titanate is used in the form of needle-like single crystals (whiskers). Usually, the fiber diameter is 0.1 to 0.5 μm, and the length is 10 to 50 μm, and the most readily available ones are 15 to 30 μm.

[0057] (5-5) Inorganic particles with thermal insulation Furthermore, for applications requiring thermal insulation, the composition may contain inorganic particles having a thermal insulation effect, such as porous or hollow inorganic particles such as silica aerogel, glass bubbles, and glass balloons; inorganic particles capable of exhibiting adhesion in an aqueous solution, such as colloidal silica and alumina hydrate (e.g., boehmite); and ceramic particles capable of scattering radiant heat, such as titanium oxide, alumina, and silica without a binder function (crystalline silica powder, amorphous silica, fumed silica, etc.).

[0058] (5-6) Other fillers In addition to the above, the raw material slurry may contain less than 5% by weight, more preferably 3% by weight or less, of the following fillers as solid contents.

[0059] Other solid fillers include neutralizing agents, lubricants, antiblocking agents, flow improvers, release agents, flame retardants, colorants, wetting agents, tackifiers, paper strength improvers, drainage agents, and pH adjusters.

[0060] (6) Dispersion medium The dispersion medium for preparing the slurry may be any medium capable of uniformly dissolving or dispersing the above-mentioned silica-based fibers, organic fibers, clay minerals, glass fibers, and other components added as required (binders, inorganic particles, etc.). For example, aromatic hydrocarbons such as toluene, ethers such as tetrahydrofuran, ketones such as methyl ethyl ketone, alcohols such as isopropyl alcohol, N-methyl-2-pyrrolidone (NMP), dimethylacetamide, dimethylformamide, dimethylsulfoxide, water, etc. can be used as necessary, and water is preferably used.

[0061] <Preparation of raw material slurry (suspension for papermaking)> The components listed above, i.e., silica-based fibers, fibrous minerals, organic fibers, and, if desired, glass fibers, as well as flocculants, binders, inorganic particles providing thermal insulation, and other fillers which are blended as required, are added in predetermined amounts to a dispersion medium and stirred to prepare a raw material slurry.

[0062] The solid content of the raw material slurry may be any concentration that allows the above components to be uniformly stirred and mixed, specifically, the solid content is 0.01 to 10% by weight, preferably 0.05 to 3% by weight.

[0063] The order of mixing the above components is not particularly limited, but it is preferable to add various fibers while stirring them in the dispersion medium. In addition, when inorganic particles are contained, they may be added after surface modification with a dispersant or the like, if necessary.

[0064] <Wet papermaking> The wet papermaking method is a method in which the raw material slurry prepared above is made into a sheet by a papermaking machine, pressed to remove water, and then dried to obtain a sheet-like product. As the papermaking machine, a cylinder papermaking machine, a Fourdrinier papermaking machine, an inclined papermaking machine, an inclined short wire papermaking machine, or a combination of these can be used.

[0065] After papermaking, before drying, during drying, or after drying, the non-combustible sheet may be molded into a desired shape. The molding can usually be performed by press molding under heating. For example, by using an embossed press as a press machine, the surface layer of the non-combustible paper can be made to have an uneven surface. A press machine capable of forming shapes such as slits may also be used.

[0066] When a long sheet is produced by continuously carrying out papermaking, dehydration, and drying, the sheet may be wound around a roll or the like to obtain a roll of the noncombustible sheet. The noncombustible sheet of the present invention, particularly when fibrous clay is used as the clay mineral, has flexibility, so that it can also be produced as a roll.

[0067] If necessary, two or more sheet layers may be laminated using various combination nets, multi-layer circular nets, various laminators, or the like.

[0068] After papermaking, the paper is dried to remove the dispersion medium. The drying temperature is at least a temperature at which the dispersion medium can be evaporated, preferably at least 80°C at which the organic fibers can be softened. Although it depends on the type of organic fiber used, it is usually 80 to 200°C, preferably 100 to 150°C.

[0069] As for the hot pressing, conventional hot pressing, preheating cold pressing, high frequency heating and the like may be used alone or in combination of two or more.

[0070] The thickness of the paper, sheet or molded product obtained in the above papermaking process can be 0.3 mm or more, 0.5 mm or more, 1 mm or more, 1.5 mm or more, 10 mm or less, 5 mm or less, 3 mm or less, or 2 mm or less. This can be appropriately selected depending on the papermaking method and application. In the noncombustible sheet of the present invention, particularly when a fibrous mineral is used as the clay mineral, clogging of the mesh during dehydration (papermaking) can be avoided, so that a sheet with a thickness of about 10 mm can be produced. On the other hand, when only a thin sheet can be obtained, a laminate may be formed by stacking a plurality of sheets as necessary. When stacking a plurality of sheets, it is preferable to bond them with an inorganic binder. As the inorganic binder, the inorganic binders listed for the raw material slurry can be used.

[0071] <Composition of fireproof paper or sheet> The fireproof paper or sheet according to the present invention is obtained by wet papermaking the raw material slurry as described above, and then removing the dispersion medium by drying. In the fire-retardant paper or sheet of the present invention thus produced, the silica fibers, organic fibers, and glass fibers are randomly entangled on the sheet plane, and some of the organic fibers are fused. Furthermore, it is preferable that the silica fibers, organic fibers, and glass fibers are extended in the plane direction to form a layer.

[0072] The obtained fireproof paper or sheet may be laminated in a plurality of sheets, or may be laminated on another substrate to form a laminate. Furthermore, a decorative film or the like may be laminated, if necessary.

[0073] Examples of other substrates include inorganic fiber fabrics, blankets, metal foils, metal fiber sheets, metal plates, thermosetting resin sheets, and thermosetting resin plates. By laminating the non-flammable paper or sheet of the present invention into a laminate, it becomes possible to impart heat insulation, fire prevention and flame resistance to these substrates.

[0074] The single layer thickness of the non-combustible paper or sheet is 0.3 to 10 mm, preferably 0.5 to 5 mm, and either a thin or thick non-combustible sheet can be obtained depending on the application.

[0075] The noncombustible sheet of the present invention having the above-mentioned structure is a noncombustible sheet that can be used for fire prevention and flame resistance purposes even at temperatures of 700°C or above, which cannot be used with noncombustible sheets whose main constituent fiber is glass fiber or which use aluminum foil as a fireproof layer. Even when exposed to flames of over 1000℃, it will not ignite, ignite, decompose or burn, and can still function as a fire-resistant and flame-resistant sheet. Moreover, compared to sheets made from silica-based fibers alone, it has higher rigidity and tensile strength. Also, compared to papers whose main components are glass fibers or mineral fibers, it has more flexibility. Furthermore, depending on the basis weight of the sheet, it has a bulk density of 150 to 400 kg / m 3 Therefore, mica sheet (generally 2000kg / m 3 It is much lighter than the

[0076] <Application> The fireproof paper or sheet of the present invention can be used in various applications requiring flame resistance. In particular, it can be used in applications requiring flame resistance and fire resistance at high temperatures of 700°C or higher, which exceeds the heat resistance temperature of glass fiber and the melting point of aluminum, such as a covering material for sound absorbing materials, a car body protection sheet used in automobile sheet metal work, and a fireproof and fire-resistant sheet used in glass factories and foundries. In particular, it can be made to have a composition that does not contain non-fibrous particles such as those problematic with rock wool, or inorganic particles that cause problems with powder falling, and can be used as a fireproof, fireproof, and heat-insulating sheet used in manufacturing sites of materials for precision instruments where the inclusion of such inorganic particles is a problem. EXAMPLES

[0077] [Evaluation method] (1) Nonflammable (1-1) Flame exposure test 1 As shown in FIG. 1, the sheet to be evaluated (150 mm × 150 mm, thickness 1.6 mm ± 0.2 mm) 10 was fixed to a cationic steel plate 11 using adhesive tape 12, and the sheet 10 was heated for 10 minutes using a horizontally fixed burner flame 13 (the flame was adjusted so that the temperature at a point 5 mm from the heated side of the sample was 1000°C), and the presence or absence of ignition or combustion, as well as the condition of the sheet after the flame exposure test (the presence or absence of cracks, holes, etc.) were visually observed. If the sheet did not ignite or burn, and no cracks or holes were found on the sheet after the flame exposure test, it was rated as "OK." On the other hand, if the sheet shape could not be maintained due to ignition, melting, or decomposition of the components, it was rated as "NG."

[0078] (1-2) Flame exposure test 2 As shown in FIG. 2, the sheet to be evaluated (150 mm × 30 mm, thickness 1.6 mm ± 0.2 mm) 15 was held in a cantilevered state by clips 14, and the free end of the sheet (the end of the sheet not clamped by clips 14) was heated by a burner for 10 minutes. The presence or absence of combustion, ignition, or bursting of fire, as well as the retention of the sheet shape after the flame exposure test, were visually observed. If no ignition or combustion was observed and the sheet shape was retained after exposure to flame, it was rated as "OK." On the other hand, if the sheet ignites or burns, even if it is non-flammable, if the original sheet shape is deformed due to thermal shrinkage or the sheet strength (rigidity) is reduced so that it can no longer maintain the cantilever state, as in sheet 15' shown in Figure 3, it will be evaluated as "NG."

[0079] (2) Flexibility A 15 cm×15 cm sheet (thickness: about 1.6 mm±0.2 mm) 10 was held by hand on both sides and bent as shown in Fig. 4. If it could be bent, it was further folded in half. The sheet was rated as "X" if cracks occurred during the bending test or bending test, as "△" if it could be bent but cracks occurred during the bending test, as "◯" if it could be bent and no cracks occurred in the bending test, and as "◎" if it could be bent and returned to its original sheet shape after bending.

[0080] [Raw materials and production of non-combustible paper] <Raw materials> (1) Silica-based inorganic fibers BELCOTEX® 110 from BELCHEM GmbH (composition: AlO 1.5 18〔(SiO 2 ) 0.6 (SiO 1.5 OH) 0.4 〕) chopped strands (fiber diameter 9 μm, fiber length 3 to 5 mm). Fibers that were heat-treated at 300°C (heat-treated silica-based inorganic fibers) or that were not heat-treated (untreated silica-based inorganic fibers) were used.

[0081] (2) Fibrous minerals Sepiolite Average primary particle size: 30-70μm, bulk density: 0.13-0.15g / ml Kaolinite Kaolin from Hayashi Pure Chemical Industries (for research and experiment purposes)

[0082] (3) Glass fiber Glass fibers with diameters of 5 to 9 μm and lengths of 3 to 9 mm were used.

[0083] (4) Organic fibers Pulp fiber (fiber diameter 20~30μm) Polyester fiber (fiber diameter 5-10μm, fiber length 3-9mm)

[0084] (5) Binder Acrylic latex was used as the organic binder. Colloidal silica (Snowtex 30 (registered trademark)) was used as the inorganic binder. Snowtex 30 is a colloidal solution of monodispersed silica nanoparticles (amorphous) with an average primary particle diameter of 10 to 20 nm, and the specific surface area of ​​the silica particles is 130 to 280 m 2 / g.

[0085] Flocculant Aqueous solution of aluminum sulfate (1.0% by weight) Polyacrylamide

[0086] <Preparation of suspension for papermaking and sheet making by papermaking method: No.1-10> The above raw material components were added and mixed in a container containing 2000cc of water to prepare a papermaking suspension with the composition (weight % of solid content) shown in Table 1. The components were added and mixed in the following order: silica-based inorganic fiber, glass fiber, mineral clay, organic fiber, binder, and flocculant (aluminum sulfate, polyacrylamide). Polyacrylamide was added in the range of 1cc to 5cc while checking the state of the flocs in the papermaking suspension.

[0087] The suspension for papermaking prepared above was poured into a wet forming machine (filtration mesh screen #80 (openings 180 to 200 μm)) and dehydrated by suction. After dehydration, the suspension was heated and dried under pressure for 10 minutes using a hot press (100°C). This resulted in sheets measuring 150 mm x 150 mm x approximately 1.2 to 2.0 mm thick. Three sheets were produced for each suspension. The average yield calculated from the solid content of the suspension was 80% to 90%. After the papermaking, the paper was heated and pressed for 10 minutes using a hot press heated to 100° C. As a result, a sheet of 150 mm×150 mm×thickness of about 1.6±0.2 mm was obtained. The obtained sheet was subjected to the above-mentioned flame exposure tests 1 and 2 to evaluate the non-combustibility and bending resistance. The results are shown in Table 1.

[0088] [Table 1]

[0089] No.5 is a case where the fiber component is organic fiber only. The main component of the sheet is sepiolite, but the organic fiber content is high at 20% by weight, so ignition and combustion were observed. In flame exposure test 2, the sheet was no longer able to maintain its shape 5 minutes after the start of the test. Regarding bending and softness, it was flexible, probably due to the high organic fiber content.

[0090] No. 2 is a sheet mainly made of heat-treated silica-based fibers, and is thought to not shrink at high temperatures. However, after the organic fibers were burned away by exposure to flame, there was nothing to bind the fibers together, and the sheet became like an aggregate of silica-based fibers (flocculated). In this state, the sheet strength was insufficient, and in flame exposure test 2, sagging was observed as shown in Figure 4.

[0091] On the other hand, No.6 is a case where glass fiber was used instead of silica fiber as the main fiber. In flame exposure test 1, melting of glass fiber was observed in the flame exposed part. It is considered that the sheet shape cannot be maintained if a flame exposure test is conducted on the sheet alone.

[0092] No. 3 is a sheet mainly composed of untreated silica-based fibers. Thermal shrinkage occurs during flame exposure test 1, but as shown in Figure 1, since the sheet 10 is fixed to the steel plate 11, large cracks occurred in the sheet after the flame exposure test. After flame exposure test 2, the sheet shape could not be maintained due to thermal shrinkage and the burnt organic fibers.

[0093] No. 10 is a sheet mainly composed of untreated silica-based fibers, just like No. 3. It contains clay minerals (sepiolite), but does not contain glass fibers, so cracks occurred after flame exposure test 1. This is thought to be due to thermal shrinkage of the untreated silica-based fibers.

[0094] No. 7 is a sheet mainly made of untreated silica-based fibers like No. 3, but contains glass fibers. It is a sheet that is not expected to undergo thermal shrinkage due to exposure to flames, but since it does not contain clay minerals, the sheet became flocculent after flame exposure test 1.

[0095] When the inorganic fiber constituting the sheet is only glass fiber (No. 8), even if it contains clay minerals, the fiber components disappear at high temperatures such as 1000°C, so it is thought that the sheet shape will be difficult to maintain.

[0096] No.1 is a sheet mainly composed of heat-treated silica-based fibers, and also contains clay minerals, glass fibers, and organic fibers. Despite the small amount of glass fibers (2% by weight), it has paper-like flexibility, is non-flammable, and no holes or cracks were observed even after flame exposure test 1. In addition, the sheet shape and strength were maintained even after flame exposure test 2. Furthermore, it is flexible and no cracks were observed in the bending test.

[0097] No. 4 is a case where untreated silica-based fiber is used as the main fiber of the sheet. Because clay minerals, glass fiber, and organic fiber coexist, it has paper-like flexibility and is non-flammable. No holes or cracks were observed even after post-flame exposure testing.

[0098] No.9 is a case where kaolinite was used instead of sepiolite as a clay mineral. Although untreated silica-based fiber was used, it was non-flammable and was able to maintain the sheet shape even after exposure to flames. However, it lacked flexibility, and when a flexibility test like that shown in Figure 4 was conducted, it bent and cracked.

[0099] A microscope photograph (100x magnification) of the surface of the No. 4 fireproof sheet is shown in Figure 5. It can be seen that the silica-based fibers, organic fibers, and glass fibers are randomly oriented and intertwined. Figure 6 shows a micrograph (70x magnification) of No. 4 in the thickness direction (cut surface). It was possible to confirm that the fibers were layered and stacked. In some parts of the micrograph, the fibers appear to be stretched in the thickness direction and entangled, but this is thought to be due to the fact that some of the fibers were pulled in the thickness direction (cut direction) when cut.

[0100] Figure 7 shows a microscope photograph (100x) of the No. 4 fireproof sheet in the planar direction after the flame exposure test. It was confirmed that the fibers were kept in an entangled state. This is thought to have allowed the sheet to maintain the strength necessary to maintain its shape even after exposure to flame. [Industrial Applicability]

[0101] The fire-resistant paper or sheet of the present invention will not ignite or ignite when exposed to flames, and can retain its sheet shape even at high temperatures of over 800°C, at which point glass fibers melt. Furthermore, since it does not contain non-fibrous particles such as shot or inorganic particles, it can be used in applications where flame resistance and fire resistance are required under severe conditions where powder fall is a problem, or in applications where fire resistance and flame resistance must be imparted to a substrate.

Claims

1. The present invention comprises a silica-based inorganic fiber; a layered silicate mineral; and an organic fiber, At least a portion of the silica-based fiber and the organic fiber are entangled in a planar direction, A fire-retardant paper or sheet in which a portion of the organic fibers is fused in the thickness direction or planar direction.

2. 2. The fire-retardant paper or sheet according to claim 1, further comprising glass fibers, a portion of the glass fibers being entangled with the silica-based fibers or the glass fibers.

3. 3. The fireproof paper or sheet according to claim 1, comprising 40 to 85% by weight of the silica-based inorganic fiber, 10 to 40% by weight of the layered silicate mineral, 3 to 10% by weight of the organic fiber, and 0 to 15% by weight of the glass fiber.

4. 3. The fire-retardant paper or sheet according to claim 1, wherein the layered silicate mineral is a fibrous clay mineral.

5. 3. The fire-retardant paper or sheet according to claim 1 or 2, which is prepared by papermaking an aqueous suspension containing silica-based inorganic fibers; layered silicate minerals; organic fibers; and, if desired, glass fibers.

6. The fireproof paper or sheet according to claim 1 or 2, having a thickness of 0.3 to 10 mm.

7. Bulk density: 150-400 kg / m 3 7. The non-combustible paper or sheet according to claim 6,

Citation Information

Patent Citations

  • Waste gasscirculating type positive pressure sintering process

    JP1977075602A